Does Delaying Surgical Resection After Neoadjuvant Chemoradiation Impact Clinical Outcomes in Locally Advanced Rectal Adenocarcinoma? A Single Institution Experience - Nguyen, Phuong (Am J Clin Oncol, 2018)
OBJECTIVES: Surgical resection for locally-advanced rectal adenocarcinoma commonly occurs 6–10 weeks after completion of neoadjuvant chemoradiation (nCRT). We sought to determine the optimal timing of surgery related to the pathological complete response (pCR) rate and survival endpoints. METHODS: Retrospective analysis of 92 patients treated with nCRT followed by surgery from 2004 – 2011 at our institution. Univariate and multivariate analysis was performed to assess the impact of timing of surgery on local regional control (LRC), distant failure (DF), disease-free survival (DFS), and overall survival (OS). RESULTS: Time-to-surgery was ≤8 wks (group A) in 72% (median 6.1 weeks) and >8 weeks (group B) in 28% (median 8.9 weeks) of patients. No significant differences in patient characteristics, LRC, or pCR rates were noted between groups. Univariate analysis revealed that group B had significantly shorter time to DF (group B median 33 months; group A median not reached, p=0.047) and shorter OS compared to group A (group B median 52 months; group A median not reached, p=0.03). Multivariate analysis revealed that increased time-to-surgery showed a significant increase in DF (HR 2.96, p=0.02) and trends towards worse OS (HR 2.81, p=0.108) and DFS (HR 2.08, p=0.098). CONCLUSIONS: We found that delaying surgical resection longer than 8 weeks after nCRT was associated with an increased risk of DF. This study, in combination with a recent larger study, question the recent trend in promoting surgical delay beyond the traditional 6–10 weeks. Larger, prospective databases or randomized studies may better clarify surgical timing following nCRT in rectal adenocarcinoma.